Validation of HAV biomarker 2A for differential diagnostic of hepatitis A infected and vaccinated individuals using multiplex serology. Issue 43 (13th October 2017) - Bohm, Katrin; Filomena, Angela; Schneiderhan-Marra, Nicole; Krause, Gérard; Sievers, Claudia
Highlights: A new diagnostic tool to distinguish vaccinated from infected immune response for HAV. Clinical validation of HAV multiplex serology. High sensitivity, specificity and accuracy to measure HAV infection and vaccination. Using Luminex® technology to facilitate sero-epidemiological studies. Abstract: Background: Worldwide about 1.5 million clinical cases of hepatitis A virus (HAV) infections occur every year and increasingly countries are introducing HAV vaccination into the childhood immunization schedule with a single dose instead of the originally licenced two dose regimen. Diagnosis of acute HAV infection is determined serologically by anti-HAV-IgM detection using ELISA. Additionally anti-HAV-IgG can become positive during the early phase of symptoms, but remains detectable after infection and also after vaccination against HAV. Currently no serological marker allows the differentiation of HAV vaccinated individuals and those with a past infection with HAV. Such differentiation would greatly improve evaluation of vaccination campaigns and risk assessment of HAV outbreaks. Here we tested the HAV non-structural protein 2A, important for the capsid assembly, as a biomarker for the differentiation of the immune status in previously infected and vaccinated individuals. Methods: HAV antigens were recombinantly expressed as glutathione-S-transferase (GST) fusion proteins. Using glutathione tagged, magnetic fluorescent beads (Luminex®), the proteins were affinity purified and used in a multiplex serological assay. The multiplex HAV assay was validated using 381 reference sera in which the immune status HAV negative, vaccinated or infected was established using the Abbott ARCHITECT® HAVAb-IgM or IgG, the commercial HAV ELISA from Abnova and documentation in vaccination cards. Results: HAV multiplex serology showed a sensitivity of 99% and specificity of 95% to detect anti-HAV IgG/IgM positive individuals. HAV biomarker 2A allowed the differentiation between previously infected and vaccinated individuals. HAV vaccinated individuals and previously infected individuals could be identified with 92% accuracy. Conclusion: HAV biomarker 2A can be used to differentiate between previously HAV-vaccinated and naturally infected individuals. Within a multiplex serological approach this assay can provide valuable novel information in the context of outbreak investigations, longitudinal population based studies and evaluations of immunization campaigns.